A MnCo-MOF / GO composite material and its preparation method and application
By using graphene oxide-supported MnCo-MOF composite materials in the catalytic oxidation of ethyl acetate, the problem of easy agglomeration of MOFs materials is solved, the catalytic efficiency and stability are improved, and efficient ethyl acetate catalysis and green environmental protection are achieved. Catalyst preparation.
Patent Information
- Application Number
- CN202410889705.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-04
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-07-04
AI Technical Summary
Existing MOFs materials are prone to agglomeration during catalytic oxidation of ethyl acetate, resulting in poor stability and low catalytic efficiency, and fail to effectively solve the emission problems of ethyl acetate.
Graphene oxide is used as a support to support MnCo-MOF, and the dispersion and catalytic efficiency of MOFs are improved through its mechanical strength and conductivity, forming MnCo-MOF/GO composite materials, and synergistically improve catalytic efficiency and stability by using the synergistic action of the bimetal system.
It significantly improves the conversion rate and stability of MnCo-MOF/GO composites in catalytic oxidation of ethyl acetate, reduces the preparation cost, conforms to the green chemistry concept, and is suitable for the catalytic and other esterification reactions of ethyl acetate.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and more specifically, relates to a MnCo-MOF / GO composite material and a preparation method and application thereof. Background Art
[0002] Ethyl acetate is an important VOCs (volatile organic compounds). As a substitute for traditional benzene-based industrial solvents, it has developed rapidly and is widely used in the chemical, coating, printing and other industries. Excessive emissions of ethyl acetate will have a serious impact on the quality of the ecological environment and human health. Catalytic oxidation technology is an economical and efficient VOCs tail-end treatment technology. In order to reduce the emission of VOCs such as ethyl acetate, MOFs (metal organic framework) materials can be applied to the treatment of ethyl acetate. MOFs have high specific surface area, controllable pore structure and abundant metal active sites, which can significantly improve the catalytic reaction efficiency of ethyl acetate. However, MOFs materials also have their own disadvantages, such as weak coordination bonds and mechanical strength, easy agglomeration during the preparation process, and poor stability.
[0003] Patent publication number CN116637654A discloses the use of cobalt source, manganese source and dimethylimidazole as precursors to prepare CoMn-MOF, and the removal rate of volatile organic compounds such as toluene obtained by the prepared CoMn-MOF is 90%. However, this solution still does not solve the disadvantage that MOFs materials are easy to agglomerate; under this premise, it is not disclosed whether CoMn-MOF has a good catalytic oxidation effect on ethyl acetate. Summary of the invention
[0004] In view of the above-mentioned existing technical problems, the primary purpose of the present invention is to provide a method for preparing a MnCo-MOF / GO composite material. The MnCo-MOF / GO composite material prepared by the preparation method not only has excellent catalytic oxidation effect on ethyl acetate, but also has excellent stability.
[0005] The second object of the present invention is to provide a method for preparing a MnCo-MOF / GO composite material to obtain a MnCo-MOF / GO composite material.
[0006] The third object of the present invention is to provide an application of a MnCo-MOF / GO composite material in the catalytic oxidation of ethyl acetate.
[0007] A fourth object of the present invention is to provide a method for catalytic oxidation of ethyl acetate.
[0008] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0009] The present invention claims a method for preparing a MnCo-MOF / GO composite material, comprising the following steps:
[0010] S1. preparing graphene oxide;
[0011] S2. Mix a manganese source, a cobalt source and a solvent to obtain a MnCo mixed precursor solution; mix the MnCo mixed precursor solution and a graphene oxide solution to obtain a mixed solution; mix the mixed solution and an organic ligand, heat to react, and post-treat to obtain a MnCo-MOF / GO composite material.
[0012] The inventor found through research that single metal MOFs are easy to reunite and have poor stability during the catalytic process, and the efficiency of existing catalysts in the catalytic oxidation process of ethyl acetate is also to be improved. The present invention adopts graphene oxide (GO) as a carrier to load composite metal MOFs to form a composite material. Graphene oxide has excellent mechanical strength. When it is used as a carrier, the two-dimensional layered structure can provide a good supporting structure, significantly improve the dispersibility of MOFs, avoid MOFs from reuniting during the reaction, ensure that more active sites are exposed in the reactant, and then maintain and improve the high-efficiency performance of the composite material. On the other hand, graphene oxide also has excellent electrical conductivity. As an electronic conductor, it can effectively promote electron transfer, further improve the catalytic efficiency and selectivity of ethyl acetate. Due to the mechanical strength and chemical stability of graphene oxide, and its better dispersibility for MOFs, the stability and service life of the composite material are also further improved.
[0013] Furthermore, the present invention has found through research that the bimetallic system of Mn and Co provides a variety of electron transfer channels, which is helpful for the generation and conversion of catalytic reaction intermediates. Through the synergistic effect of the multi-metal system, the MnCo-MOF / GO composite material shows a higher conversion rate in the catalytic synthesis of ethyl acetate, thereby improving the reaction efficiency.
[0014] The present invention utilizes cheap and abundant agricultural and forestry solid waste as precursor materials, which greatly reduces the preparation cost of the catalyst; in addition, the agricultural and forestry solid waste is converted into high-value-added catalytic materials, which conforms to the concepts of green chemistry and sustainable development and reduces environmental pollution. The present invention can not only overcome the problems of high cost and waste of resources in the prior art, but also significantly improve the stability and catalytic efficiency of the catalyst, and has broad application prospects. The present invention is suitable for the synthesis of ethyl acetate and has a wide range of potential applications, and can be used for other esterification reactions and different types of organic catalytic reactions.
[0015] Preferably, in step S2, the molar ratio of the manganese source to the cobalt source is 1 to 5: 1 to 5. Further preferably, the molar ratio of the manganese source to the cobalt source may be 1: 0.8 to 1.2; or the molar ratio of the manganese source to the cobalt source may be 1: 2.8 to 3.2; or the molar ratio of the manganese source to the cobalt source may be 2.8 to 3.2: 1. Under this preferred ratio, the MnCo-MOF / GO composite material has a better catalytic efficiency for ethyl acetate.
[0016] Preferably, in step S2, the ratio of the MnCo mixed precursor to the graphene oxide is 1 to 12: 1. Further preferably, the ratio of the MnCo mixed precursor to the graphene oxide is 6 to 10:1.
[0017] Preferably, in step S2, the molar ratio of the MnCo mixed precursor to the organic ligand is 1-2:1.
[0018] Preferably, in step S2, the temperature of the mixing reaction is 100-120°C.
[0019] Preferably, the organic ligand is selected from terephthalic acid, trimesic acid, 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid or isophthalic acid.
[0020] Preferably, the post-treatment comprises: collecting the precipitate by centrifugation, washing, and drying.
[0021] Preferably, the manganese source and the cobalt source are nitrate solutions of the corresponding metals.
[0022] Preferably, in step S1, the method for preparing graphene oxide is:
[0023] (1) heating the biomass to 300-500° C. under an inert atmosphere to obtain a carbonized product;
[0024] (2) The carbonized product is oxidized under the action of a mixed acid and an oxidant to obtain graphite oxide;
[0025] (3) The washed graphite oxide is mixed with a solution and subjected to ultrasonic treatment to exfoliate the graphite oxide into graphene oxide.
[0026] Preferably, in step (1), the biomass is selected from one or more of straw (such as corn straw), peanut shells, rice husks, bagasse, and corn cobs.
[0027] Preferably, the mixed acid is a mixture of concentrated sulfuric acid and phosphoric acid. Further preferably, the volume ratio of concentrated sulfuric acid to phosphoric acid is 8 to 10:1. The use of mixed acid in the present invention can: (1) enhance the oxidation effect. Concentrated sulfuric acid is a strong oxidant, which can effectively oxidize biomass carbon materials and peel off graphene layers. Phosphoric acid can play a buffering role in the reaction process, control the severity of the reaction, and reduce the occurrence of side reactions. (2) Improve stability: The use of mixed acid can improve the stability of the reaction and reduce the risk of explosion caused by excessively intense reactions. Phosphoric acid helps to stabilize the reaction temperature and prevent local overheating. (3) Improve the quality of the sheet: The mixed acid system can reduce the damage to the graphene sheet while maintaining high oxidation ability, thereby improving the quality of GO and the integrity of the sheet structure. The above-mentioned mixed acid can synergistically improve the dispersion and uniformity of the graphene oxide sheet.
[0028] Preferably, the oxide is selected from one or more of potassium permanganate, sodium nitrate, potassium dichromate and hydrogen peroxide.
[0029] Preferably, in step (1), the heating time is 2 to 4 hours.
[0030] Preferably, in step (2), the specific operation of oxidation is: mixing the carbonization product, the mixed acid and the oxidant, first stirring and reacting in an ice bath for 2 to 3 hours, and then heating to 35 to 40° C. and reacting for 1 to 2 hours.
[0031] Preferably, in step (3), the ultrasonic treatment time is 1.5 to 2.5 hours. The ultrasonic treatment conditions are: power of 200 to 500 W, frequency ≥ 20 kHz.
[0032] Furthermore, the present invention seeks to protect a method for preparing a MnCo-MOF / GO composite material and an MnCo-MOF / GO composite material obtained by the preparation.
[0033] Furthermore, the present invention seeks to protect the use of the above-mentioned MnCo-MOF / GO composite material in the catalytic oxidation of ethyl acetate.
[0034] Furthermore, the present invention also claims a method for catalytically oxidizing ethyl acetate, wherein ethyl acetate gas or gas containing ethyl acetate is introduced into the MnCo-MOF / GO composite material for reaction.
[0035] Preferably, the temperature of the catalytic oxidation is ≥150°C. Further preferably, the temperature of the catalytic oxidation is 170-250°C. In the present invention, the mass proportion of the transition metal oxide can be 150°C, 160°C, 70°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, etc., or an interval range formed by any of the above values, such as 160-180°C, 190-220°C, etc., and the present invention is not limited thereto.
[0036] Preferably, the flow rate of the ethyl acetate gas is 180-220 mL / min.
[0037] Preferably, the dosage of the MnCo-MOF / GO composite material is 100-200 mg, and the concentration of ethyl acetate gas is 80-200 ppm.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The present invention adopts graphene oxide as a carrier to load MnCo-MOF, and prepares a MnCo-MOF / GO composite material. The MnCo-MOF / GO composite material has not only an excellent catalytic oxidation effect on ethyl acetate, but also excellent stability. DETAILED DESCRIPTION
[0040] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0041] Example 1 Preparation of a MnCo-MOF / GO composite material
[0042] (1) The corn stalks were washed, dried and crushed to 100 mesh. The crushed solid waste was heated to 450°C in nitrogen and maintained for 3 h to obtain a carbonized product. Potassium permanganate (KMnO4) was slowly added to the carbonized product in a mixed solution of concentrated sulfuric acid (H2SO4) and phosphoric acid (H3PO4) (volume ratio of 9:1). The mixture was stirred in an ice bath for 2.5 h and then heated to 37°C for 1.5 hours to obtain graphite oxide.
[0043] The graphite oxide was repeatedly washed with deionized water until the pH of the washing solution was close to neutral. The graphite oxide was dispersed in 200 mL of deionized water and subjected to ultrasonic treatment (power of 300 W and frequency of 20 kHz) for 2 h to exfoliate the graphite oxide into graphene oxide (GO). The GO dispersion was frozen at -80 ° C for 24 hours and then freeze-dried to obtain graphene oxide (GO) powder.
[0044] (2) 0.25 mmol of Mn(NO3)2·4H2O and 0.25 mmol of Co(NO3)2·6H2O (molar ratio 1:1) were mixed and dissolved in deionized water to obtain a MnCo mixed precursor solution. GO (15 mg, molar ratio of GO to MnCo mixed precursor was 1:10) was added to N,N-dimethylformamide (DMF, 20 mL) and ultrasonically treated for 1 h. The MnCo mixed precursor solution was slowly added to the DMF solution of dispersed GO at room temperature and stirred by magnetic stirring for about 30 min to obtain a uniform solution.
[0045] (3) 0.5 mmol of terephthalic acid (H2BDC) was dissolved in a uniform solution to obtain an organic ligand solution, which was stirred magnetically for about 30 minutes. The synthesized precursor solution was then placed in a reactor and heated at 120°C for 24 hours. After the reaction was completed, it was cooled to room temperature, the brown-black precipitate was collected by centrifugation, and washed several times with deionized water, ethanol, and DMF solvent. The obtained sample was dried in a vacuum oven at 80°C for 12 hours to prepare a MnCo-MOF / GO composite material.
[0046] Example 2 Preparation of a MnCo-MOF / GO composite material
[0047] The difference between this embodiment and embodiment 1 is that Mn(NO3)2·4H2O and Co(NO3)2·6H2O are mixed in a molar ratio of 1:2.
[0048] Example 3 Preparation of a MnCo-MOF / GO composite material
[0049] The difference between this embodiment and embodiment 1 is that Mn(NO3)2·4H2O and Co(NO3)2·6H2O are mixed in a molar ratio of 1:3.
[0050] Example 4 Preparation of a MnCo-MOF / GO composite material
[0051] The difference between this embodiment and embodiment 1 is that Mn(NO3)2·4H2O and Co(NO3)2·6H2O are mixed in a molar ratio of 2:1.
[0052] Example 5 Preparation of a MnCo-MOF / GO composite material
[0053] The difference between this embodiment and embodiment 1 is that Mn(NO3)2·4H2O and Co(NO3)2·6H2O are mixed in a molar ratio of 3:1.
[0054] Comparative Example 1
[0055] The difference between this comparative example and Example 1 is:
[0056] Step (1) is not performed; in step (2), only Mn(NO3)2·4H2O is dissolved in deionized water; in step (2), the MnCo mixed precursor solution is not added to the DMF solution in which GO is dispersed. Mn-MOF is prepared.
[0057] Comparative Example 2
[0058] The difference between this comparative example and Example 1 is:
[0059] Step (1) is not performed; in step (2), only Co(NO3)2·6H2O is dissolved in deionized water; in step (2), the MnCo mixed precursor solution is not added to the DMF solution in which GO is dispersed. Co-MOF is prepared.
[0060] Comparative Example 3
[0061] The difference between this comparative example and Example 1 is:
[0062] The step (1) is not performed; in the step (2), the MnCo mixed precursor solution is not added to the DMF solution in which GO is dispersed. MnCo-MOF is prepared.
[0063] Comparative Example 4
[0064] The difference between this comparative example and Example 1 is:
[0065] In step (2), only Mn(NO3)2·4H2O is dissolved in deionized water to prepare Mn-MOF / GO.
[0066] Comparative Example 5
[0067] The difference between this comparative example and Example 1 is:
[0068] In step (2), only Co(NO3)2·6H2O is dissolved in deionized water to prepare Co-MOF / GO.
[0069] Comparative Example 6
[0070] The difference between this comparative example and Example 1 is:
[0071] In step (2), Mn(NO3)2·4H2O and Ni(NO3)2·6H2O are dissolved in deionized water to prepare a MnNi-MOF / GO composite material.
[0072] Comparative Example 7
[0073] The difference between this comparative example and Example 1 is:
[0074] In step (2), Co(NO3)2·6H2O and Cu(NO3)2·3H2O are dissolved in deionized water to prepare a CoCu-MOF / GO composite material.
[0075] Test Case
[0076] Experimental setup: 150 mg of the composite material prepared in the above examples or comparative examples was loaded into a fixed bed reactor system.
[0077] Reaction gas preparation: The concentration of ethyl acetate reaction gas is prepared to be 100 ppm.
[0078] Reaction conditions: The flow rate of the reaction gas was set at 200 mL / min.
[0079] The reaction temperature was set at 190°C.
[0080] Reaction process: Start the reaction gas flow, maintain the reaction temperature and flow rate, and carry out the catalytic oxidation reaction of ethyl acetate. Continuously monitor the concentration change of ethyl acetate in the reaction gas and calculate its conversion rate.
[0081] The conversion rate (Conversion rate, η) of ethyl acetate was calculated according to the following formula:
[0082]
[0083] C in is the concentration of ethyl acetate before entering the reactor (ppm). out is the concentration of ethyl acetate after leaving the reactor (ppm).
[0084] Stability test: The composite materials prepared in Example 1 and Comparative Example 3 were subjected to continuous catalytic oxidation reaction for 16 hours under the above conditions, and then the catalytic activity of the composite materials prepared in Example 1 and Comparative Example 3 was tested again. The test results are shown in Table 1 below.
[0085] Table 1
[0086] catalyst Reaction temperature / ℃ Conversion rate of ethyl acetate / % Example 1 <![CDATA[Mn1Co1-MOF / GO]]> 190 97.62 Example 1 Stability <![CDATA[Mn1Co1-MOF / GO]]> 190 97.62 Example 2 <![CDATA[Mn1Co2-MOF / GO]]> 190 91.63 Example 3 <![CDATA[Mn1Co3-MOF / GO]]> 190 95.13 Example 4 <![CDATA[Mn2Co1-MOF / GO]]> 190 92.02 Example 5 <![CDATA[Mn3Co1-MOF / GO]]> 190 96.33 Example 1 <![CDATA[Mn1Co1-MOF / GO]]> 185 95.56 Comparative Example 1 Mn-MOF 185 60.32 Comparative Example 2 Co-MOF 185 69.61 Comparative Example 3 MnCo-MOF 185 70.21 Comparative Example 3 Stability MnCo-MOF 185 62.5 Comparative Example 4 Mn-MOF / GO 185 68.54 Comparative Example 5 Co-MOF / GO 185 71.12 Comparative Example 6 MnNi-MOF / GO 185 72.34 Comparative Example 7 CoCu-MOF / GO 185 74.15
[0087] From the data of Examples 1 to 5 above, it can be seen that the MnCo-MOF / GO composite material provided by the present invention has an excellent catalytic oxidation effect on ethyl acetate, and its ethyl acetate conversion rate is ≥ 91.63%. Furthermore, the MnCo-MOF / GO composite material provided by the present invention can optimally reach 97.62%.
[0088] It can be seen from the stability test of Example 1 and Example 1 that the MnCo-MOF / GO composite material prepared by the present invention has excellent stability, and the conversion rate of ethyl acetate does not change after the continuous catalytic oxidation reaction for 16 hours.
[0089] It can be seen from Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 that when the composite material does not use graphene oxide as a carrier, its conversion rate of ethyl acetate is significantly worse than that of the composite material in Example 1 of the present application.
[0090] It can be seen from Example 1, Comparative Example 4 and Comparative Example 5 that the bimetallic system of Mn and Co used in the present invention provides a variety of electron transfer channels, which is helpful for the generation and conversion of catalytic reaction intermediates. Through the synergistic effect of the multi-metal system, the MnCo-MOF / GO composite material shows a higher conversion rate in the catalytic synthesis of ethyl acetate, thereby improving the reaction efficiency.
[0091] It can be seen from Example 1, Comparative Example 6 and Comparative Example 7 that when other metal composites are used, the conversion rate of ethyl acetate is significantly worse than that of the composite material of Example 1 of the present application.
[0092] Table 2 shows the effect of the MnCo-MOF / GO composite material prepared in Example 1 on the catalytic oxidation activity of ethyl acetate at different temperatures.
[0093] Table 2
[0094]
[0095] It can be seen from Table 2 that at different reaction temperatures, the MnCo-MOF / GO composite material has excellent conversion rate of ethyl acetate.
[0096] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to require the widest possible range that can be imagined, and the embodiments presented herein are demonstrated by the applicant's actual test results. Therefore, the applicant's intention is that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges therein, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.
Claims
1. Application of MnCo-MOF / GO composite material in catalytic oxidation of ethyl acetate, characterized in that: The preparation method of the MnCo-MOF / GO composite material comprises the following steps: S1. preparing graphene oxide; S2. mixing a manganese source, a cobalt source and a solvent to obtain a MnCo mixed precursor solution; mixing the MnCo mixed precursor solution and a graphene oxide solution to obtain a mixed solution; mixing the mixed solution and an organic ligand, heating the reaction, and post-treating to obtain a MnCo-MOF / GO composite material; In the step S1, the preparation method of graphene oxide is: (1) heating the biomass to 300-500°C under an inert atmosphere to obtain a carbonized product; (2) The carbonization product is oxidized under the action of a mixed acid and an oxidant to obtain graphite oxide; (3) mixing the washed graphite oxide with a solution and subjecting it to ultrasonic treatment to exfoliate the graphite oxide into graphene oxide; The mixed acid is a mixture of concentrated sulfuric acid and phosphoric acid; The organic ligand is selected from terephthalic acid, trimesic acid, 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid or isophthalic acid.
2. The application according to claim 1, characterized in that: In the step S2, the molar ratio of the manganese source to the cobalt source is 1-5:1-5.
3. The application according to claim 1, characterized in that: In the step S2, the molar ratio of the MnCo mixed precursor to the graphene oxide is 1 to 12:
1.
4. The use according to claim 1, characterized in that: In the step S2, the molar ratio of the MnCo mixed precursor to the organic ligand is 1-2:
1.
5. The use according to claim 1, characterized in that: In step S2, the temperature of the heating reaction is 100-120°C.
6. The use according to claim 1, characterized in that: In the step (1), the biomass is selected from one or more of straw, peanut shells, rice husks, bagasse, and corn cobs.
